Development and Psychometric Testing of the Older Adults' Technology Use at Home Scale - Fatemeh Sadat Izadi-Avanji; Malihe Yazdani Darki (Iran University of Medical Sciences, 2020)
Background: Aging is associated with changes in some capabilities. Using technology can help older adults to continue living independently at home. This study aimed to develop the Older Adults' Technology Use at Home Scale (OATUHS) and evaluate its psychometric properties in the Iranian context. Methods: It was a sequential-exploratory mixed-method study for the development and psychometric testing of OATUHS. A draft scale with 15 items was generated based on a literature review and interviews with 20 older adults. The psychometric properties were assessed by testing the scale on 200 older adults referring to the Urban Comprehensive Health Service Centers of Kashan province, Iran. The multistage cluster sampling method was used to recruit the participants. Then, the face, content, and construct validities as well as internal consistency and stability reliability were assessed. The obtained data were analyzed using the SPSS, version 16. Also, the exploratory factor analysis was conducted using the principal component analysis and the varimax rotation method to determine the factors of the scale. Results: The OATUHS consisted of 12 items. Exploratory factor analysis resulted in two factors explaining 69.6% of the variance. The internal consistency of the scale was acceptable (r=0.88); it was 0.93 for the "in-kitchen technologies" and 0.87 for "out-of-kitchen technologies" dimensions. Besides, an intraclass correlation coefficient of 0.95 was estimated between the test and retest scores. Conclusion: The OATUHS is a valid and reliable tool for the measurement of the use of technology by older adults at home, in daily life.